1970
DOI: 10.1088/0022-3727/3/4/424
|View full text |Cite
|
Sign up to set email alerts
|

The emission spectrum of thermoluminescent dosimetry grade lithium fluoride

Abstract: The change in the emission spectrum of irradiated thermoluminescent lithium fluoride is investigated as a function of specimen temperature. The emission peak energy rises with temperature and it is suggested that a temperature dependence upon the luminescent efficiency of the recombination processes is responsible rather than an association of specific emission peaks with individual glow peaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…all five glow peaks are present), while removing any past history which might affect the thermoluminescent output. The shape of the glow-curve is not altered by annealing between 400 ' c and 600 ' C (Nakajima 1968). The peak height method was used in the present work so that the peak or peaks responsible for any shift in t'he emission spectrum with exposure, as reported by Bloch, could be distinguished.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…all five glow peaks are present), while removing any past history which might affect the thermoluminescent output. The shape of the glow-curve is not altered by annealing between 400 ' c and 600 ' C (Nakajima 1968). The peak height method was used in the present work so that the peak or peaks responsible for any shift in t'he emission spectrum with exposure, as reported by Bloch, could be distinguished.…”
Section: Methodsmentioning
confidence: 98%
“…The thermoluminescent emission spectrum of LiF (TLD-100) has been studied by a number of investigators (Zimmerman and Cameron 1964, Gorbics 1967, Strash and Madey 1969. Harris and Jackson (1970) observed the emission spectrum of LiF (TLD-700) as a function of temperature with a rapid-scanning spectrometer. They found that the thermoluminescent emission shifted to shorter wavelengths for higher temperature glow peaks, but no variation of the emission spectrum with dose was observed over the range 1 krad to 1 Mrad for any of the peaks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their rates of decay on thermal annealing have been found to be equal to the rates of decay of the principal thermoluminescent glow peaks (Jackson and Harris 1970). The spectrum of emitted light is sufficiently constant at all temperatures to indicate that the same photon emission process occurs once electrons have been released from their traps (Harris and Jackson 1970), but the precise details of this process remained to be defined. Titanium is known to be an important constituent of dosimetry grade LiF and new evidence is presented here to demonstrate its role in the thermoluminescence process.…”
Section: Introductionmentioning
confidence: 99%
“…Emission spectra of LiF-TLD 100 have also been studied (Kathuria et al 1974;Crittenden et al 1974;Harris and Jackson 1970;Bloch 1968;Ellis and Rossiter 1969;Jain et al 1973;Fairchild et al 1978;Townsend et al 1983), and are found to be similar to spectra for other alkali halides, in that, the spectra are the same for all glow peaks, only the relative heights of different emission bands change. Most of the early studies give emission as a broad band around 400 nm.…”
Section: Tl Emission Spectramentioning
confidence: 93%
“…Most of the early studies give emission as a broad band around 400 nm. The variations in maxima positions under certain conditions were claimed (Bloch 1968; Harris and Jackson 1970;Sagastibelza and Alvarez-Rivas 1981). Fairchild et al (1978a) showed that emission at all glow peaks can be fitted to three Gaussian shaped bands at 3-01, 2.90 and 2.71 eV, the relative heights of which change at different glow peaks.…”
Section: Tl Emission Spectramentioning
confidence: 95%